Ethical and Legal Considerations When Obtaining Informed Consent for Treating Minors of High-Conflict Divorced or Separated Parents. (July 2013) - Shumaker, David; Medoff, David
Obtaining informed consent for the treatment of minors from parents in high conflict and who are either divorced or separated is a crucial, initial, and ongoing aspect of the treatment process that merits awareness of both ethical and legal considerations. Parents in these cases frequently differ in their views of the need for treatment, their choice of treatment providers, and/or their goals of treatment. A parent or minor will often request the other parent remain uninvolved in treatment. In order to avoid negative treatment outcomes, licensing complaints, and/or civil liability, clinicians need resources from which to obtain critical information regarding the informed consent process. This article provides an overview of these considerations and a decision-tree model for obtaining informed consent when working with these complex families.